TrisOxine abiotic siderophores for technetium complexation: radiolabeling and biodistribution studies - Julien Leenhardt; Alexandre Biguet Petit Jean; Florian Raes; Emilien N'Guessan; Marlène Debiossat; Clémence André; Sandrine Bacot; Mitra Ahmadi; Nicolas de Leiris; Loïc Djaileb; Catherine Ghezzi; Marie-Dominique Brunet; et al. (SpringerOpen, 2023)
Abstract Background Despite the development of positron emission tomography (PET), single photon emission computed tomography (SPECT) still accounts for around 80% of all examinations performed in nuclear medicine departments. The search for new radiotracers or chelating agents for Technetium-99m is therefore still ongoing. O-TRENSOX and O-TRENOX two synthetic siderophores would be good candidates for this purpose as they are hexadentate ligands based on the very versatile and efficient 8-hydroxyquinoline chelating subunit. First, the radiolabeling of O-TRENOX and O-TRENSOX with 99mTc was investigated. Different parameters such as the quantity of chelating agent, type of reducing agent, pH and temperature of the reaction mixture were adjusted in order to find the best radiolabeling conditions. Then an assessment of the partition coefficient by measuring the distribution of each radiosynthesized complex between octanol and phosphate-buffered saline was realized. The complex's charge was evaluated on three different celluloses (neutral, negatively charged P81 and positively charged DE81), and finally in vivo studies with biodistribution and SPECT imaging of [99mTc]Tc-O-TRENOX and [99mTc]Tc-O-TRENSOX were performed. Results The radiolabeling studies showed a rapid and efficient complexation of 99mTc with both chelating agents. Using tin pyrophosphate as the reducing agent and a minimum of 100 nmol of ligand, we obtained the [99mTc]Tc-O-TRENOX complex with a radiochemical purity of more than 98% and the [99mTc]Tc-O-TRENSOX complex with one above 97% at room temperature within 5 min. [99mTc]Tc-O-TRENOX complex was lipophilic and neutral, leading to a hepatobiliary elimination in mice. On the contrary, the [99mTc]Tc-O-TRENSOX complex was found to be hydrophilic and negatively charged. This was confirmed by a predominantly renal elimination in mice. Conclusions These encouraging results allow us to consider the O-TRENOX/99mTc and O-TRENSOX/99mTc complexes as serious candidates for SPECT imaging chelators. This study should be continued by conjugating these tris-oxine ligands to peptides or antibodies and comparing them with the other bifunctional agents used with Tc.